The role of perceived green marketing and brand equity on green purchasing decision - Hasna Sanidewi; Eristia Lidia Paramita (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2018)
The purpose of this study is to describe the role of perceived green marketing and brand equity on customers green purchasing decision in Indonesia. We conducted qualitative research using five informants who are customers of The Body Shop Indonesia, one of the companies implementing green marketing. The primary data was collected through the interviews, observations, and supported documents, as triangulation. The collected data was filtered and categorized to have a clear analysis. The results were shown that the informants perceived The Body Shop’s green marketing as a respectable action to reduce the negative impact of the firms’ business activities. Green marketing has developed and influenced The Body Shop brand positively. It leads the informants to insert their environmental consideration in their purchasing decision.